Exploring Key Factors Determining US Consumer Preferences for Growing over Buying Fruit in Pre-Covidian and Covidian Times - Meike Rombach; David L. Dean; Tim Baird (Horticulturae, 2021)
This study provides insights for managers in the food retail sector, the horticultural industry, actors involved in community gardening and farmers’ markets. It proposes a model that investigates key factors determining US consumer preferences for growing fruit over buying it in pre-Covidian and Covidian times. For this purpose, an online survey with a sample of 383 US residents was conducted. Partial least squares structural equation modelling shows that subjective knowledge about fruit and the perceived impact of COVID-19 are the most important drivers of preferences for growing over buying in Covidian times. The impact of COVID-19 had no relevance for the pre-Covidian times. For both scenarios, only age and gender as socio-demographic factors were found to influence subjective knowledge and the perceived impact of COVID-19. Other sociodemographic factors were not found to have any impact.